Prospective randomized double blind comparison of analgesic efficacy of single shot epidural bupivacaine with or without dexamethasone in patients undergoing lower abdominal surgeries - Rayamajhi, Anuj Jung; Bhattarai, Balbrishna; Shah, Birendra Prasad (Journal of Society of Anesthesiologists of Nepal, 2015)
Background: Epidural block with local anaesthetic with or without additives is being used for perioperative analgesia. Various additives have been used to enhance the effect of regional blocks including epidural blocks. This study aimed to investigate the effect of adding a single shot epidural dexamethasone to bupivacaine on postoperative analgesia and dose of rescue analgesics used. Methods: A prospective, randomized, double blinded study was conducted in 90 adult patients undergoing lower abdominal surgery. The patients were randomized into two groups. Group 1 received 9ml of 0.5% bupivacaine plain with 1 ml of normal saline. Group 2 received 9ml of 0.5% bupivacaine plain 9 ml with 1 ml of dexamethasone (4mg). After standard balanced anesthesia technique, patients were observed in postoperative period for pain and hemodynamic variables accordingly. Results: Our study showed significantly longer duration of analgesia of 468 minutes (almost 8 hours) when dexamethasone was added to bupivacaine for single shot epidural injection compared to 271 minutes (approximately 4 and half hours) when bupivacaine alone was used (p<0.001). Consumption of rescue analgesic, Tramadol, was significantly lower in dexamethasone group in 24 hours (169.31±50.82 mg in Group 1 and 114.77±60.59mg in Group 2, p<0.001). No adverse events were noted. Conclusion: Addition of dexamethasone to bupivacaine for single shot epidural block almost doubled the duration of analgesia. Single shot epidural block using bupivacaine with addition of dexamethasone provides effective post operative analgesia and significantly reduced the postoperative rescue analgesic requirement. Journal of Society of Anesthesiologists of Nepal 2015; 2(2): 46-51